Navigation Factors Affecting Shipping Safety in The Indonesian Archipelago Sea Lane (ALKI) - Budi Mantoro (Syntax Corporation, 2025)
Shipping safety is a crucial aspect in the sea transportation sector, especially in the Indonesian Archipelago Sea Route (ALKI) which is a strategic route for national and international ship traffic. This study aims to identify and analyze navigation factors that affect shipping safety in ALKI. The method used in this study is a quantitative approach with secondary data analysis and interviews with related parties, such as port authorities, captains, and maritime regulators. The results of the study show that several main factors that affect shipping safety at ALKI include hydrographic and oceanographic conditions, ship traffic density, the existence of navigational aids, the level of compliance with shipping regulations, and the competence and readiness of the ship crew. In addition, extreme weather factors and the uncertainty of the marine environment also contribute to the risk of maritime accidents. The implications of these findings lead to recommendations to improve navigation infrastructure, strengthen regulations, and improve the competence of human resources in the maritime industry to reduce the risk of accidents in ALKI waters.